Research of the Effect of Bearing Stiffness and Gear Helix Angle on Vibration Noise of Gear Reducer - Zhou Jianxing; Sun Wenlei; Cui Quanwei (Jixie chuandong)
The dynamics model of the cylindrical gear transmission system is built in consideration of the time-varying mesh stiffness and gear errors.The dynamic load of the bearing is taken as the excitation,the vibration and noise radiation of the gear reducer is researched by using FEM/BEM,then the time history of node vibration displacement and noise spectrum of the gearbox are obtained,and the effect of the excitation of frequency doubling of mesh frequency on the gearbox vibration and noise radiation are illustrated.The effect of bearing stiffness and helix angle on vibration and noise radiation are researched,then the rule of dynamic load with bearing stiffness,the rule of noise radiation with bearing stiffness and helix angle are obtained.The study provides useful theoretical guideline to the design of the gearbox.